2022
DOI: 10.3390/jpm12050825
|View full text |Cite
|
Sign up to set email alerts
|

Association between Statin Use and Risk of Parkinson’s Disease: Evidence from 18 Observational Studies Comprising 3.7 Million Individuals

Abstract: The potential impact of statins on the risk of Parkinson’s disease (PD) is still controversial; therefore, we conducted a comprehensive meta-analysis of observational studies to examine the effect of statin use on the risk of PD. We searched electronic databases, such as PubMed, EMBASE, Scopus, and Web of Science, for articles published between 1 January 2000 and 15 March 2022. Cohort studies which examined the association between statins and PD risk in the general population were also included. Two authors as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“… 61 Up‐to‐date evidence from 15 observational studies revealed that statins use has a protective role against PD risk. 62 Following adjusting of confounding factors, the findings of this study showed that long‐duration statin use was linked with a decreased risk of PD. There was no significant decrease in the risk of PD in short‐term statin users.…”
Section: Protective Role Of Statins In Pdmentioning
confidence: 72%
See 1 more Smart Citation
“… 61 Up‐to‐date evidence from 15 observational studies revealed that statins use has a protective role against PD risk. 62 Following adjusting of confounding factors, the findings of this study showed that long‐duration statin use was linked with a decreased risk of PD. There was no significant decrease in the risk of PD in short‐term statin users.…”
Section: Protective Role Of Statins In Pdmentioning
confidence: 72%
“…In addition, no significant difference in the reduction in the risk of PD was observed between men and women. 62 This study indicated that only long‐term statin therapy is effective against the development and progression of PD regardless of sex factor.…”
Section: Protective Role Of Statins In Pdmentioning
confidence: 76%
“…Furthermore, the comorbidity burden of T2DM may include other conditions that have been associated with the risk of developing PD. For instance, it has been reported that the use of statins in the context of dyslipidemia decreases the risk of PD 22 , as well as the use of beta-blockers commonly used to treat hypertension 23 . Other commonly sees metabolic disturbance seen in metabolic syndrome is in serum uric acid levels; low uric acid has been associated with morbidity, severity progression, non-motor symptoms, and motor complications of PD 24 .…”
Section: Discussionmentioning
confidence: 99%
“…A star system is used to judge the study quality with a maximum of 9 stars (4 stars for selection, 2 stars for comparability, and 3 stars for outcome). A study with 9 stars was classified as high quality, 7–8 stars as moderate, and <7 stars as low quality [ 5 , 12 , 23 ].…”
Section: Methodsmentioning
confidence: 99%